Certain properties of a new subclass of analytic functions with negative coefficients involving q-derivative operator - Aini Janteng; Andy Liew Pik Hern (AIP Publishing, 2024)
This study focused on the class of functions which are analytic in the open unit disk. The subclass of analytic functions consisting of univalent functions. In this study, we also focused on the subclass of functions with negative coefficients. Recently, many researchers investigated the q-derivative operator. By considering functions with negative coefficients and q-derivative operator, this study defined a new subclass of analytic functions. Apart from that, certain properties of functions belonging to the new class of functions which include coefficient estimates, growth result and extreme points were obtained.